SARAJEVO’S READING PRIMER BY MILJENKO JERGOVIĆ - Giergiel, Sabina (Porównania, 2012)
The article focuses on issues connected to methods of depicting place of origin (i.e. Sarajevo) in a collection entitled Historijska čitanka. The story about the town becomes a testimony of an annihilated world and a protest against manipulating memory. In the writer’s picture, his place of origin is not semantically and axiologically indifferent, it is filled with meanings understood exclusively by its former dwellers. Elements of reality are a common basis for agreement between members of the generation of people who were born in the sixties sharing identical experience of war and division of the country as well as a feeling of lost opportunities.